CULTURA DE DIATOMACEAS - Takahashi, Ari Tomi; Imai, Marie; Grosskpof, Marcio Rogério (Revista Nerítica, 1986)
The present note gives information on outdoor mass production of Diatoms Algae for feeding différents species of shrimp of the Genus Penaeus.